An Examination of the Interpersonal Theory of Suicide's Tenets among Women with Bulimic-Spectrum Pathology. Issue 2 (3rd April 2021) - Lieberman, Amy; Joiner, Thomas E.; Duffy, Mary E.; Wonderlich, Stephen A.; Crosby, Ross D.; Mitchell, James E.; Crow, Scott J.; Peterson, Carol B.; Le Grange, Daniel; Bardone-Cone, Anna M.
Abstract : Objective : Suicide attempts and self-injurious behaviors (SIBs) are known to be elevated among people with bulimia nervosa (BN). The aim of the current study was to examine the Interpersonal-Psychological Theory of Suicide (IPTS) as a framework for understanding, assessing, and mitigating suicidal behavior among women with BN. The IPTS suggests that for individuals to enact lethal suicide attempts, they must have both the desire to die (consisting of thwarted belongingness and perceived burdensomeness) as well as the capability to die (often acquired through repeated exposure to provocative or painful experiences). Method : Two-hundred and four women with eating disorders, the majority of whom met criteria for a current DSM-IV diagnosis of BN, completed measures from which proxies for IPTS variables were formed. Bivariate correlations and multiple regressions tested main effects and interactions of study variables. Tests of the difference between dependent correlations probed differential associations between study variables and suicidal ideation versus suicidal behavior. Results and Conclusions : Results yielded considerable but not unalloyed support for the theory, with desire to die variables (particularly perceived burdensomeness) more strongly associating with suicidal ideation than behavior, and the opposite holding true regarding capability. These findings suggest that the IPTS may provide a useful framework for understanding, assessing, and mitigating suicide risk among individuals with BN.